Assessment of knowledge and attitude regarding use of contraceptive methods among women at selected rural area, Ambala, Haryana, India - Kaur, Amandeep; Kaur, Baljinder; Gupta, Abhishek; Singh, Amardeep (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Family planning refers to practices that help individuals and couples to attain certain objectives like to avoid unwanted births. The objectives of study were to assess the knowledge and attitude regarding use of contraceptive methods among women. Also to find out correlation between knowledge and attitude scores regarding use of contraceptive methods among women and to determine association of level of knowledge and attitude regarding use of contraceptive methods among women with selected demographic variables. Methods: The research approach adopted for the study was quantitative research approach. The present study was carried out on the 200 women of reproductive age of village Rajouli, Ambala, Haryana selected by purposive sampling technique. The tools used for data collection were structured knowledge questionnaire and attitude scale (3 point likert’s scale). Validity was ensured through consultation with the experts and reliability of knowledge questionnaire was established using Kuder’s Richardson-20 formula whereas of attitude scale by split half method which is fund to be (r = 0.82) and (r = 0.80) respectively. Formal permission from sarpanch of village Rajouli. Results: Descriptive and inferential statistics were used to analyze the data. Findings of study revealed that more than half (51.5%) of the women were in the age group of 25-31 years. Results further illustrated that (38%) of women had average knowledge and (44%) moderately favorable attitude regarding use of contraceptive methods. There was significant association of level of knowledge of women with income per month (44.7), type of family (16.2), gap between first and second child (16.9), source of information about contraceptives (14.1) whereas level of attitude of women was found to be statistically significant with age (13.6), educational status (89.5), occupational status (20.2), family income per month (17.2), duration of marriage (19.7), number of children (17.9). There was significant positive correlation between knowledge and attitude scores as evident by computed ‘r’ value of 0.13. Conclusions: Hence, there is a need to create awareness among women of reproductive age group regarding contraceptive methods.